Erythrocyte’s aging in microgravity highlights how environmental stimuli shape metabolism and morphology - Dinarelli, S.; Longo, G.; Dietler, G.; Francioso, A.; Mosca, L.; Pannitteri, G.; Boumis, G.; Bellelli, A.; Girasole, M. (Scientific reports, 2018)
The determination of the function of cells in zero-gravity conditions is a subject of interest in many different research fields. Due to their metabolic unicity, the characterization of the behaviour of erythrocytes maintained in prolonged microgravity conditions is of particular importance. Here, we used a 3D-clinostat to assess the microgravity-induced modifications of the structure and function of these cells, by investigating how they translate these peculiar mechanical stimuli into modifications, with potential clinical interest, of the biochemical pathways and the aging processes. We compared the erythrocyte’s structural parameters and selected metabolic indicators that are characteristic of the aging in microgravity and standard static incubation conditions. The results suggest that, at first, human erythrocytes react to external stimuli by adapting their metabolic patterns and the rate of consumption of the cell resources. On longer timeframes, the cells translate even small differences in the environment mechanical solicitations into structural and morphologic features, leading to distinctive morphological patterns of aging.